Apports Du Modele Numerique De Terrain Mnt A La Modelisation Du Relief Et Des Caracteristiques Physiques Du Bassin Versant Du Moyen Beht En Amont Du Barrage El Kansera (Sillon Sud Rifain, Maroc) - Laabidi, Ahmed; El Hmaidi, Abdellah; Gourari, Lahcen; El ABASSI, Mourad (European Scientific Journal, ESJ, 2016)
The watershed of the Beht River occupies the southwest part of the Sebou watershed with an area of 4,603.77 km2. It starts in the Causse of Middle Atlas, drains the northern edge of central Morocco and ends in the rifan south wrinkles at the level of dam El Kansera. The geographical information system (GIS) and ASTER images with a resolution of 30m have been of great use for creating thematic maps and automatic extraction of a multitude of parameters and physiographic indices of this watershed. These parameters, very characteristic, allow to assess the weight of the geomorphology on surface water flow and the influence of the latter by the risk of erosion and of flooding which have a very negative consequences on human and material plan, at the level of the studied watershed.